2016
DOI: 10.1107/s1600576716009171
|View full text |Cite
|
Sign up to set email alerts
|

Diamond drumhead crystals for X-ray optics applications

Abstract: Thin (<50 mm) and flawless diamond single crystals are essential for the realization of numerous advanced X-ray optical devices at synchrotron radiation and free-electron laser facilities. The fabrication and handling of such ultra-thin components without introducing crystal damage and strain is a challenge. Drumhead crystals, monolithic crystal structures composed of a thin membrane furnished with a surrounding solid collar, are a solution ensuring mechanically stable strain-free mounting of the membranes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…Is it possible to eliminate the strain induced by laser cutting? In our previous studies (Kolodziej et al, 2016) we found that annealing diamond crystals in air at a temperature of 630-650 C for 3 h may substantially reduce strain induced in the process of laser cutting or ablation. The strain is caused by the graphitization of the machined surfaces.…”
Section: Impact Of Diamond Crystal Clampingmentioning
confidence: 96%
“…Is it possible to eliminate the strain induced by laser cutting? In our previous studies (Kolodziej et al, 2016) we found that annealing diamond crystals in air at a temperature of 630-650 C for 3 h may substantially reduce strain induced in the process of laser cutting or ablation. The strain is caused by the graphitization of the machined surfaces.…”
Section: Impact Of Diamond Crystal Clampingmentioning
confidence: 96%
“…The utility of an x-ray FEL oscillator (XFELO) has been under study for a decade [7][8][9][10][11][12][13][14] making use of resonators based upon Bragg scattering from high-reflectivity diamond crystals [15][16][17][18][19]. The development of these crystals is a major breakthrough in the path toward an XFELO.…”
Section: Introductionmentioning
confidence: 99%
“…Outcoupling was done by switching to a status with large transmission and near-zero reflection. Several techniques for radiation outcoupling, including a small fast rotation or heating with a laser pulse, can be employed and are currently being studied (57)(58)(59). We chose the backscattering Bragg geometry, as it provides a large angular acceptance while reducing the bandwidth (Table 1 and Fig.…”
Section: X-ray Laser Oscillatormentioning
confidence: 99%